Celiac Disease Causes, Treatment and Extent of its Spread in Zliten City - Anweder, Hanan Mohammed; Abosalah, Hanan Ismail; Shabek, Hajer Mosbah (The annual Scientific Conference for Under and Postgraduate Students at the University., 2023)
Celiac disease, also known as gluten sensitivity or abdominal disease, is a condition resulting from the body's inability to tolerate gluten. This study aimed to determine a prevalence of wheat sensitivity in Zliten City and gather information about the disease. The study included statistical data on patients diagnosed with wheat sensitivity in Zliten City between 2020 and 2022, registered at Al-Gawilat poly Clinic. The prevalence of this disease was 0.124% in the city of Zliten during this period. A paper questionnaire was distributed to individuals with the disease who visited Al-Gawilat poly Clinics. The sample consisted of 74 individuals diagnosed with wheat sensitivity. The study revealed that 41% of the patients were male, while 55.4% were female. The majority of the study sample fell within the age range of 20 to under 40 years, accounting for 59.7% of the total sample. Blood tests were the primary method of diagnosing the disease, accounting for 66.2% of the total sample, while 33% underwent intestinal biopsy. The study found that 53.5% of the sample had no relatives suffering from the same disease. Furthermore, most individuals in the sample had other accompanying diseases, including anemia in 40.3% of the total sample and skin dryness and redness in 22.2% of the total sample. Approximately 54.2% of the sample adhered to the gluten-free diet regularly. The main reason for non-compliance with the diet was the unavailability of specialized foods for the disease, accounting for 64.1% of a total. The majority of respondents who were affiliated with associations that provided their meals reported that these associations did not supply all the necessary foods, with a rate of 90.1%. Also, they indicated that the health authorities did not fulfill the required awareness role, with a rate of 63.9%. Therefore, it is recommended to follow a gluten-free diet as a primary measure, and organizations should provide special foods for individuals with wheat sensitivity. Extensive surveys and research are also recommended to determine the actual number of patients and gather relevant information about this disease, with a focus on Zliten City and Libya in general, to raise awareness among patients.
Keywords: Gluten sensitivity; Wheat sensitivity; Malnutrition; Celiac disease; Abdominal disease